Contribution of a LysM domain-containing protein regulated by VicRK to Streptococcus sanguinis virulence - Eduardo M. Franco; Lívia A. Alves; Isabela Camargo; Geovanny C. Salvatierra; Maíra Terra Garcia; Tsute Chen; Juliana C. Junqueira; Débora C. Bastos; Renata O. Mattos-Graner (Virulence)
Streptococcus sanguinis is a commensal member of the oral microbiome involved in opportunistic cardiovascular infections. In the present study, we investigated the contribution of ssa_0094, a gene strongly regulated by the two-component system VicRK, to functions associated with biofilm formation, immune evasion, and cardiovascular virulence. In silico analysis showed that ssa_0094 encodes a protein with a LysM domain, which is highly conserved among S. sanguinis. Although not an ubiquitous gene, several commensal streptococcal species of the oronasopharynx and zoonotic strains of Streptococcus suis harbor ssa_0094 homologues. A ssa_0094 isogenic mutant (SK0094) showed defects in initiating biofilms on saliva-coated surfaces, reduced hydrophobicity, and lower production of amyloid-like components when compared to the parent strain (SK36) or to the complemented mutant (SK0094+), although it showed mild changes in DNA release and production of H2O2. Deletion of ssa_0094 also impaired S. sanguinis binding to multiple human glycoproteins of plasma and/or extracellular matrix (ECM) (plasminogen, fibronectin, fibrinogen, fibrin, type I collagen, and elastin) and promoted clear increases in C3b deposition and in induction of NEtosis by neutrophils of peripheral blood. Moreover, SK0094 showed impaired invasiveness into HCAEC cells and reduced ex vivo persistence in human blood, but no clear change in virulence in a Galleria mellonella infection model. These findings indicate that ssa_0094 is highly conserved within S. sanguinis strains and required for biofilm initiation as well as for multiple functions of immune evasion and cardiovascular virulence in S. sanguinis in a host-specific fashion.